Psychometric Validation of the Korean Version of the Camberwell Assessment of Need for the Elderly in Individuals with Dementia - Myonghwa Park; Sun Kyung Kim; Miri Jeong; Song Ja Lee; Seon Hwa Kim; Jinha Kim; Dong Young Lee (Elsevier, 2018)
Purpose: The prevalence of dementia has increased rapidly with an aging Korean population. Compared to those without dementia, individuals with dementia have more and complex needs. In this study, the Korean version of the Camberwell Assessment of Need for the Elderly (CANE-K) was evaluated to determine its suitability for individuals with dementia in Korea. Methods: The CANE-K was developed following linguistic validation. The reliability of the measurement was examined with Cronbach α coefficient. The factor structure and construct validity were evaluated by performing exploratory factor analysis and confirmatory factor analyses. Pearson's correlation coefficients with related measures were used to ensure concurrent validity. Results: Four factors extracted with exploratory factor analysis and confirmatory factor analyses validated the model structure (χ2 = 367.25, p < .001, goodness-of-fit index = .84, adjusted goodness-of-fit index = .80, root mean square error of approximation = .07, and comparative fit index = .83). Items on the CANE-K loaded on the four factors in a range between .40 and .80. The output of Pearson's correlation coefficient with cognitive impairment, behavioral problems, activities of daily living, and caregiver burden showed acceptable concurrent validity. Conclusion: The CANE-K showed a reasonable degree of reliability and validity. Therefore, it has good potential to appropriately measure the needs and unmet needs of those with dementia. Keywords: dementia, needs assessment, patient-centered care, validation studies